2013
DOI: 10.1002/ajmg.b.32199
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide copy number scan identifies disruption of PCDH11X in developmental dyslexia

Abstract: Developmental dyslexia (DD) is a complex heritable disorder with unexpected difficulty in learning to read and spell despite adequate intelligence, education, environment, and normal senses. We performed a whole genome copy number variations (CNV) scan on 11 dyslexic families consisting of 14 dyslexic subjects and 24 non dyslexic members using 1.8 million combined SNP and CNV markers. We found CNVs affecting protocadherin genes in six dyslexics from three families, while none among the non-dyslexic control mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…SETBP1 deletions have been described in cases of expressive language impairment with mild ID (24,38,93). Inherited deletion of the X-chromosomal gene PCDH11X together with de novo deletion of its human-specific Y-chromosome counterpart PCDH11Y was found in a child with severe speech delay, and a study of dyslexia families reported duplication or deletion of PCDH11X in three of eleven families examined (151,181). PCDH11X and PCDH11Y are expressed predominantly in the brain and encode protocadherins, a class of molecules involved in cell adhesion and signaling.…”
Section: Structural Variation In Language-related Disordersmentioning
confidence: 99%
“…SETBP1 deletions have been described in cases of expressive language impairment with mild ID (24,38,93). Inherited deletion of the X-chromosomal gene PCDH11X together with de novo deletion of its human-specific Y-chromosome counterpart PCDH11Y was found in a child with severe speech delay, and a study of dyslexia families reported duplication or deletion of PCDH11X in three of eleven families examined (151,181). PCDH11X and PCDH11Y are expressed predominantly in the brain and encode protocadherins, a class of molecules involved in cell adhesion and signaling.…”
Section: Structural Variation In Language-related Disordersmentioning
confidence: 99%
“…However, a longitudinal study of the human prefrontal cortex showed that PCDH11X transcript levels were highest in newborn males, decreased throughout childhood, and were equally low in adults of both sexes [ 51 ]. Duplication and deletion of this region are associated with both developmental dyslexia [ 56 ] and non-syndromic language delay [ 57 ].…”
Section: Reviewmentioning
confidence: 99%
“…This genetic diversity in humans affects both disease and normal phenotypic variation. Presence of CNVs alters the transcriptional and translational levels of overlapping or nearby genes by disrupting the coding structure or by altering gene dosage thereby conferring differential susceptibility to complex diseases [ 14 18 ].…”
Section: Introductionmentioning
confidence: 99%